Rapid rollout of a pacemaker home monitoring service during the 2020 COVID-19 pandemic. (14th October 2021) - Shurlock, J; Gratton, B; Wilson, L; Heatley, R; Roach, M; Dayer, M; Furniss, G
Abstract: Introduction: In an effort to reduce non-essential face to face contact during the COVD pandemic our pacemaker service was restructured in March 2020 to home monitoring only. Home monitors were issued at implant and wound reviews were done remotely via photo messages at one month or if prompted by the patient. Existing patients were given monitors on an ad hoc basis. A dedicated physiologist worked off site on home monitoring clinics. We assessed the impact on our service and on patient experience of these changes one year after implementation. Methods: Baseline characteristics of age at implant and distance of home address from hospital were collected from all patients undergoing pacemaker home monitoring. Patients were surveyed using an adapted version of the Generic Short Patient Experiences Questionnaire (GS-PEQ). Comparison was made with our standard face-to-face follow-up model (1, 3, and 12 months). Results: Data was collected for 326 patients. 233 received a new permanent pacemaker from March 2020 onwards and 93 existing patients were issued with a home monitor. Average age at pacemaker implant was 80.6 years (±9.9 years). The average one-way distance from home to outpatient clinic saved was 15.1 miles (±10.4 miles). 567 face-to-face appointments were saved. On an average day the off-site physiologist reviewed over 100 patient records a day, contacted 10 patients by phone and dictated reports on 20 patients (14 clinic patients and 6 alerts). Of patients surveyed 88% agreed with the statement "I feel safe being cared for solely with a remote monitoring service" and 84% agreed with the statement "I receive the same standard of care via remote monitoring and face-to-face appointments". Time saved by avoiding a face to face appointment was more than 1 hour for 90% of respondents. Respondents requested communication of reassuring monitoring, the ability to contact the pacing team in the event of concerns and clearer instructions for the home monitoring device. Only 34% of newly implanted patients were able to send a photo message of their wound without prompting. We did not get a post procedure photo in 38% and the rest either spoke to us about the wound or had a face-to face visit. There was a significant difference in mean age between those who sent a photo (73.7 years) and those who didn't (81.4 years) (P=0.0006). Conclusion: Rapid role out of a remote monitoring service for permanent pacemakers across a large county was feasible, produced significant savings in clinic time and was well received by patients. There were significant time savings for physiologists and patients. However remote wound monitoring in elderly patients was problematic due to the difficulty of sending photo messages. FUNDunding Acknowledgement: Type of funding sources: None.